Today's Police and Sheriff Recruits Insights from the Newest Members of America's Law Enforcement Community - Castaneda, Laura Werber (RAND Corporation, 2010)
For much of the past decade, police and sheriff's departments faced considerable challenges in attracting and retaining recruits. This volume summarizes a 2008-2009 survey fielded to recent police officer and sheriff's deputy recruits nationwide. The authors focus on how understanding modern recruits can help departments refine their recruitment practices and develop a workforce well suited to community-oriented policing.